Syntactic Analysis On Noun Phrase In English Goods Advertisements Along Jalan Slamet Riyadi Surakarta - Komariah, Siti; , Dra. M. Laila, M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This research paper deals with syntactic analysis noun phrases used in English goods advertisement slogans along Jalan Slamet Riyadi Surakarta. The purpose of this research paper is to identify the constituents and the constituent functions of the noun phrases used in English goods advertisement slogans along Jalan Slamet Riyadi Surakarta. The type of this research is descriptive qualitative. The data source of this research is goods advertisement slogans along Jalan Slamet Riyadi Surakarta. The writer takes 23 data of noun phrases from slogans of English goods advertisements along Jalan Slamet Riyadi Surakarta. The method of collecting data is analyzing documentation and the steps are; taking pictures, selecting, noting and coding the data of NPs of English goods advertisement slogans. The method of analyzing data is descriptive technique. The analysis of the data is by referring to the context of syntax by using X-bar theory by Andrew Radford (1988) then presenting phrase structure rules and phrase markers. This study shows the construction of constituents and constituent function of noun phrases used in slogan of English goods advertisements along Jalan Slamet Riyadi Surakarta, those are: (1) N' → NP (adjunct) + N', (2) N' → NP (complement) + N, 3) N' → AP (adjunct) + N', 4) N' → N' + PP (adjunct), (5) N" → (D) + NP (adjunct) + N', (6) N" → (D) + AP (adjunct) + N', (7) N" → D + AP (adjunct) + N', (8) N" → D + N' + PP (adjunct), (9) N" → (D) + N' + PP (adjunct), (10) N" → (D) + N + PP (complement), (11) N" → D + N + PP (complement), (12) N" → (D) + NP (adjunct) + AP (adjunct) + N', (13) N" → D + NP (adjunct) + AP (adjunct) + N'.